Psychological Impacts, Hand Hygeine Practices & and Its Correlates in View of Covid-19 among Health Care Professionals in Northern States of India - Shalu Sharma; Akoijam Mamata Devi; Deepak (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The novel coronavirus disease 2019 presents an important and urgent threat to global health.190 countries with more than 300 000 confirmed cases and 14 510 deaths1. This critical situation, healthcare workers on the front line who are directly involved in the diagnosis, treatment, and care of patientswith COVID-19 are at risk of developing psychological distress and other mental health symptoms andtransmission between people through close contact and droplets2-3.Method: Descriptive correlation survey design was to assess psychological impacts, hand hygiene practices& and its correlates in view of covid-19. Probability Stratified cluster staging sampling techniques were usedto select 320 health care professionals.Result: The findings revealed that the effect of noval coronavirus covid-19 among health care professionals43.8% had mild fear, 45.9% moderate fear, and 10.3% a severe fear, and their mean value (14.58), S.D(6.96) and the variance was 48.54. Level of mild perceived stress was 46.87%, moderate perceived stresswas 44.06% and 9.06% had severe perceived stress their mean value (14.417), S.D (7.09) and variance was(50.38).Researcher is also assessing the level of practice was 94.37% had good practice, 5.62% had weakpractice their mean value (18.22), S.D (3.15) and variance was (9.92) regarding the prevention of novelcoronavirus covid -19 among Health care professionals. The correlation between fear and perceived stresswas intermediate correlation, fear and practice had weak positive correlation and in between perceivedstress and practice was showing weak positive but nearly close to no correlation. Fear was significantlyassociated with workplace was, perceived stress was significantly associated with Gender, No. of familymembers was statistically significant at P<0.05.Conclusion: Novel coronavirus covid-19 was affecting their psychological factors among health careprofessionals those are working in hospitals.